The implementation of multiculturalism learning model based on local wisdom in civic education - Japar, Muhammad; Fadhillah, Dini Nur; Komin, Wichaya; Kardiman, Yuyus; Triyanto, Triyanto; Sarkadi, Sarkadi (Jurnal Civics: Media Kajian Kewarganegaraan, 2022)
Implementing civic education learning in senior high schools has not improved students' quality as good citizens with the right civic skills. Therefore, the purpose of this study is to analyze the implementation of the multiculturalism learning model based on local wisdom in the subject of civic education. The learning model is used to instill the values of cultural diversity in students in responding to demographic changes. This is a qualitative study with data collected through interviews involving ten students and four civic education teachers in a high school in Manado, North Sulawesi. The collected data were analyzed using thematic analysis. The results indicate the values of local wisdom used as a model for multiculturalism learning. This research has implications for the culture of cooperation among students in conducting Civics learning activities in the classroom. It can act as an alternative for Civics teachers to develop the values of diligence, cooperation, and high school students' responsibility.